Synthesis and Antibacterial Activity of Isatin Schiff Base Derivative with 3-Aminoacetophenone and its Ni(II), Co(II) Transition Metals Complexes - Alsalihi, Eman I.; Al-Fahdawi, Aeed S. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2018)
The (E)-3-(3-acetylphenylimino) indolin-2-one (Bidentate) ligand type [HL], has been prepared from Isatin and 3-aminoacetophenone in the presence of KOH. In general, the ligand contains oxygen (O) and nitrogen (N) donor atoms. The reaction of Isatin and 3-aminoacetophenon was carried out in ethanol by condensation reaction at 80°C with reflux for 4 h, to form [HL] ligand type. This ligand has been used to prepare NiII and CoII complexes in the ratio of 1:1 metal-ligand. All compounds have been characterized by spectroscopic methods (Fourier transform infrared and ultravioletvisible), C.H.N, thin-layer chromatography, mass spectrum, X-ray diffraction, magnetic moment, conductivity measurements and milting point, the synthesized ligand and its metal complexes have been tested for their antibacterial activity against Staphylococcus aureus and Bacillus subtilis using agar disc diffusion method. The ligand and its complexes showed significant activities against S. aureus and B. subtilis. Our study revealed the formation of four coordinate square planar complexes around NiII and CoII metal ions.